2019
DOI: 10.1007/s00268-019-05167-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing a Medical Student's Decision to Pursue Surgery as a Career

Abstract: Background Recent match trends from the National Resident Matching Program suggest that the number of allopathic medical students (MD) pursuing general surgery is declining. This decline may have profound consequences given the surgeon shortage predicted by the Association of American Medical Colleges. Early exposure to surgery opportunities may increase a student's desire to pursue the specialty as a career. The aim of this study was to evaluate the effect surgical activities have on promoting student interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 46 publications
0
8
0
2
Order By: Relevance
“…[50][51][52] A redesign of the daily work, career advancement and scholarly demands could attract more women to surgery. [51][52][53][54] Shifting the surgical profession to support a work-life balance may encourage women to enter the profession. It appears the greatest barrier is the current structure of surgical practice.…”
Section: Discussionmentioning
confidence: 99%
“…[50][51][52] A redesign of the daily work, career advancement and scholarly demands could attract more women to surgery. [51][52][53][54] Shifting the surgical profession to support a work-life balance may encourage women to enter the profession. It appears the greatest barrier is the current structure of surgical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Different countries face an uneven distribution of medical specialties (1). Of note, the interest in a surgical career is certainly declining in some countries (2)(3)(4), and a recent systematic review (5) showed that various factors may affect choice of surgery as a career, mainly gender, features of surgical education, and acceptance of surgical lifestyle are the most important factors. The identification of the reasons that lead to the decision making process of choosing a surgical career may be used to create strategies to increase the attractiveness of this career.…”
Section: Introductionmentioning
confidence: 99%
“…As trajetórias de formação profissional de médicos comumente são marcadas por dois momentos cruciais de escolha: o que envolve a própria profissão médica e, posteriormente, a tomada de decisão pela área de especialidade. Em Medicina o exercício profissional é heterogêneo devido ao leque extenso de especialidades e subespecialidades existentes, que são marcadas por diferenças em termos da área de atuação, ambiente de trabalho e variedade de pacientes assistidos (Al--Ansari & Khafagy, 2006) Considerando que a prática médica exige uma formação que requer anos de educação continuada após a graduação (Dorsey et al, 2003), diversos estudos têm se dedicado a analisar os fatores que influenciam essa escolha, uma preocupação que tem emergido tanto no cenário internacional (Al-Ansari & Khafagy, 2006;Dorsey et al, 2003;Shelton et al, 2019), como no contexto brasileiro (Corsi et al, 2014;Millan et al, 2005).…”
unclassified
“…Estudos anteriores indicaram que a exposição precoce à especialidade na educação médica pode despertar o interesse acadêmico dos alunos e melhorar sua competência clínica (Bodenheimer & Pham, 2010;Compton et al, 2008). Por exemplo, pesquisa recente concluiu que a exposição precoce a atividades cirúrgicas emergiu como um fator que influenciou o interesse de estudantes que não tinham intenção prévia de seguir essa especialidade (Shelton et al, 2019). Ainda é desconhecido se fatores circunstanciais como este também poderiam exercer influência na escolha de outras especialidades médicas, como a Nutrologia e, dentro dela, especificamente a atuação na clínica dos TAs.…”
unclassified